AUTONOMY IN ONLINE GRAMMAR LEARNING: EFL STUDENTS’ REPORTED PRACTICE AND PERCEPTIONS - Febriana, Erica; Setyaningrahayu, Indri Retno; Murtisari, Elisabet Titik (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
Often perceived as a challenging subject among many tertiary EFL students, grammar may present more difficulties to the learners when delivered online, especially during the COVID-19 pandemic. Within such a situation, autonomous learning, which earlier literature has suggested to be crucial in helping students with grammar learning, would be even more imperative for their success. Hence, this study attempts to investigate whether EFL tertiary students in Indonesia practice autonomous learning and how they perceive learning autonomy for their online grammar class. As many as 82 Indonesian students who had taken an online intermediate grammar course in a respected private university were involved in this study. A questionnaire with close and open-ended questions was used for the data collection. The findings indicate that although students mostly had positive views towards autonomy in online grammar learning and claimed to practice it, the autonomy level tended to be low. Factors such as fatigue from online learning, distractions, overwhelming assignments, and lack of study skills, seemed to have contributed to the difficulties in practicing learner autonomy.